2002
DOI: 10.4049/jimmunol.169.10.5708
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Independent Folding and CD8αα Binding by the Nonclassical Class I Molecule, Thymic Leukemia Antigen

Abstract: The nonclassical class I molecule, thymic leukemia (TL), has been shown to be expressed on intestinal epithelial cells and to interact with CD8+ intraepithelial T lymphocytes. We generated recombinant soluble TL (T18d) H chains in bacteria as inclusion bodies and refolded them with β2-microglobulin in the presence or absence of a random peptide library. Using a mAb, HD168, that recognizes a conformational epitope on native TL molecules, we observed that protein folds efficiently in the absence of peptide. Circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 47 publications
3
26
0
Order By: Relevance
“…The crystal structure of TL revealed that its putative ligand-binding groove is too narrow to accommodate peptides or other ligands (4). This corroborates with the stable folding of TL in the absence of added ligands (5)(6)(7)(8). TL binds to CD8␣␣ homodimers with unusually high affinity relative to the interaction of CD8␣␣ or CD8␣␤ molecules with classical MHC class I molecules (5,6).…”
Section: Cd8␣␣-mediated Intraepithelial Lymphocyte Snatching Of Thymisupporting
confidence: 56%
“…The crystal structure of TL revealed that its putative ligand-binding groove is too narrow to accommodate peptides or other ligands (4). This corroborates with the stable folding of TL in the absence of added ligands (5)(6)(7)(8). TL binds to CD8␣␣ homodimers with unusually high affinity relative to the interaction of CD8␣␣ or CD8␣␤ molecules with classical MHC class I molecules (5,6).…”
Section: Cd8␣␣-mediated Intraepithelial Lymphocyte Snatching Of Thymisupporting
confidence: 56%
“…To assess directly the importance of the T18 d ␣ 3 domain in the interaction with CD8␣␣, we generated T18 d , K b , and HLA-A2 chimeric recombinant proteins from bacterial inclusion bodies (10) by swapping their constituent ␣ 3 domains to form T18…”
Section: Resultsmentioning
confidence: 99%
“…A construct encoding the T18 d cDNA in the pET23a vector has been described elsewhere (10). A K b cDNA in the pET23a vector, an HLA-A2*0201 cDNA in the pHN1 vector, and a construct containing a human ␤ 2 m cDNA were a gift from Dr. J. Altman (Emory University, Atlanta, GA) (19).…”
Section: Dna Constructionsmentioning
confidence: 99%
See 1 more Smart Citation
“…2B, our recent studies have demonstrated that TL molecules are transported to and stably expressed on the surfaces of TAP-deficient cells, such as RMA-S, 4,[10][11][12] and that most TL-specific CTLs recognize TL expressed in a TAP-independent manner. 12) Very recently, we have prepared TL tetramers free of antigenic peptides by way of peptide-independent folding with recombinant proteins produced in an Escherichia coli expression system, based on the report by Weber et al, 24) and showed that they bind to TL-specific CTLs in a TCR/CD3-dependent manner (Fig. 3A).…”
Section: Epitopes Recognized By Tl-specific Ctlsmentioning
confidence: 99%